Association between gut microbiota and gastric cancers: a two-sample Mendelian randomization study - Chang, Yuan; Gao, Guanzhuang; Feng, Cuncheng (Frontiers in Microbiology, 2024)
Background: Gastric cancer (GC) is the fifth most commonly diagnosed cancer worldwide, with its etiology attributed to a complex interplay of genetic, dietary, environmental factors, and infections such as Helicobacter pylori. Despite the known risk factors, the role of gut microbiota in the development of gastric cancer remains insufficiently explored. This study aims to elucidate the causal relationship between gut microbiota and gastric cancer using a twosample Mendelian Randomization (MR) approach.Methods: Utilizing genome-wide association study (GWAS) summary data from the MiBioGen consortium and gastric cancer datasets, we selected instrumental variables for MR analysis based on their association with specific microbiota. We employed several MR methods, including inverse variance weighted (IVW), MR-Egger, weighted median, and others, to estimate the causal effects of gut microbiota diversity on the risk of developing gastric cancer.3 Results: Our analysis identified significant associations between certain gut microbiota and gastric cancer risk. Specifically, taxa such as Clostridium sensustricto1 (OR = 0.540, 95%CI: 0.354-0.823, p = 0.004), Actinomycetales (OR = 0.756, 95%CI: 0.613-0.932, p = 0.009), andRikenellaceae (OR = 0.863, 95%CI: 0.746-0.999, p = 0.048) were found to have a protective effect against gastric cancer. Conversely, an increased risk of gastric cancer was associated with the abundance of Roseburia (OR = 1.342, 95%CI: 1.071-1.681, p = 0.011), Family XI (OR = 1.132, 95%CI: 1.012-1.267, p = 0.030), and Eubacterium brachy group (OR = 1.207, 95%CI:1.074-1.355, p = 0.002). The findings were robust across various MR methods and were not driven by any single SNP, indicating a genuine causal relationship. 4 Conclusion: Our studies have shown that there is a causal relationship between intestinal flora and gastric cancer at the genetic level. Clostridium sensustricto1, Actinomycetales, Rikenellaceae, Selenomonadales, Negativicutes, and Actinomycetaceae as having a protective role against GC, while Roseburia, Family XI, and Eubacterium brachy group were associated with an increased risk.